Identification of miRNA–mRNA regulatory network associated with the glutamatergic system in post-traumatic epilepsy rats - Zhang, Xiaoyuan; Ma, Yixun; Zhou, Fengjuan; Zhang, Mengzhou; Zhao, Dong; Wang, Xu; Yang, Tiantong; Ma, Jun (Frontiers in Neurology, 2022)
Background Glutamate is one of the most important excitatory neurotransmitters in the mammalian brain and is involved in a variety of neurological disorders. Increasing evidence also shows that microRNA (miRNA) and mRNA pairs are engaged in a variety of pathophysiological processes. However, the miRNA and mRNA pairs that affect the glutamatergic system in post-traumatic epilepsy (PTE) remain unknown. Methods PTE rats were induced by injecting 0.1 mol/L, 1 μL/min FeCl2 solution. Behavioral scores and EEG monitoring were used to evaluate whether PTE was successfully induced. RNA-seq was used to obtain mRNA and miRNA expression profiles. Bioinformatics analysis was performed to screen differentially expressed mRNAs and miRNAs associated with the glutamatergic system and then predict miRNA–mRNA interaction pairs. Real-time quantitative reverse transcription PCR was used to further validate the expression of the differential miRNAs and mRNAs. The microRNA–mRNA was subject to the Pearson correlation analysis. Results Eight of the 91 differentially expressed mRNAs were associated with the glutamatergic system, of which six were upregulated and two were downregulated. Forty miRNAs were significantly differentially expressed, with 14 upregulated and 26 downregulated genes. The predicted miRNA–mRNA interaction network shows that five of the eight differentially expressed mRNAs associated with the glutamatergic system were targeted by multiple miRNAs, including Slc17a6, Mef2c, Fyn, Slc25a22, and Shank2, while the remaining three mRNAs were not targeted by any miRNAs. Of the 40 differentially expressed miRNAs, seven miRNAs were found to have multiple target mRNAs associated with the glutamatergic system. Real-time quantitative reverse transcription PCR validation and Pearson correlation analysis were performed on these seven targeted miRNAs—Slc17a6, Mef2c, Fyn, Slc25a22, and Shank2—and six additional miRNAs selected from the literature. Real-time quantitative reverse transcription PCR showed that the expression levels of the mRNAs and miRNAs agreed with the predictions in the study. Among them, the miR-98-5p–Slc17a6, miR-335-5p–Slc17a6, miR-30e-5p–Slc17a6, miR-1224–Slc25a22, and miR-211-5p–Slc25a22 pairs were verified to have negative correlations. Conclusions Our results indicate that miRNA–mRNA interaction pairs associated with the glutamatergic system are involved in the development of PTE and have potential as diagnostic biomarkers and therapeutic targets for PTE.